PENGENDALIAN PERSEDIAAN MEDIA PENGUJIAN BPW DENGAN METODE EOQ DAN MIN-MAX DI LABORATORIUM INDUSTRI MAKANAN OLAHAN - Haerani, Tarisa Ardha; Rini, Asih Setyo; Muhammad, Irfan (JURNAL REKAYASA SISTEM INDUSTRI, 2025)
This research aims to analyze the inventory control of Buffered Peptone Water (BPW) testing media in a food industry laboratory. The company currently applies a conventional method in managing its inventory, which often leads to inefficiencies in both ordering and holding costs. Two quantitative approaches, namely Economic Order Quantity (EOQ) and Min-Max, are compared with the company's existing method to determine the most efficient alternative. Data utilized in this study consist of annual demand, ordering cost, holding cost, and lead time. The EOQ method provides an optimal order quantity of 11 units, with a total inventory cost of Rp2.506.750, while the Min-Max method recommends maintaining inventory levels between 2 units. Compared to the company’s current approach, EOQ is proven to minimize total cost and achieve cost savings of approximately 51%. The results indicate that EOQ is more effective and can be implemented as a suitable inventory control method for laboratory operations.